Development of AR Book Assemblr Teaching Materials Based on Civic Literacy on the Material of the History of the Birth of Pancasila in Class V of SDN 04 Koto Baru: Pengembangan Bahan Ajar AR Book Assemblr Berbasis Literasi Kewargaan pada Materi Sejarah Kelahiran Pancasila di Kelas V SDN 04 Koto Baru - Davina Eddyansaa; Wiwik Okta Susilawati; M. Anggrayni (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
The development of Augmented Reality (AR)-based teaching materials has emerged as an innovative approach to improving the quality of Civic Education by providing interactive and contextual learning experiences. This study aimed to develop an AR Book Assembler based on civic literacy for the topic The History of the Birth of Pancasila for fifth-grade elementary school students that meets the criteria of validity, practicality, and effectiveness. The study employed the Research and Development (R&D) method using the Four-D (4D) development model, consisting of the define, design, develop, and disseminate stages. The primary field test was conducted with fifth-grade students at SDN 04 Koto Baru, while the limited dissemination stage involved students from SDN 14 Koto Baru. Data were collected through observations, questionnaires, documentation, and learning achievement tests, and were analyzed to evaluate the product's validity, practicality, and effectiveness. The results indicated that the developed teaching material achieved excellent validity in terms of content (84.02%), language (84.10%), graphics (82.04%), Deep Learning Instructional Design (90.60%), and assessment instruments (90.80%). The practicality score reached 96.28%, indicating that the product was highly practical. Furthermore, learning mastery reached 92.85% in the primary field test and 89.47% during the limited dissemination stage, demonstrating high effectiveness. These findings indicate that the civic literacy-based AR Book Assembler is a valid, practical, and effective instructional resource for enhancing Pancasila Education learning in elementary schools.